INCREASED PULMONARY BLOOD FLOW IN NEWBORNS WITH CYANOTIC CONGENITAL HEART DEFECTS AND DUCTUS-DEPENDENT PULMONARY BLOOD FLOW: RESULTS AND FEATURES OF OUTPATIENT POSTOPERATIVE FOLLOW-UP - Anzhelika Mykhailovska; Olga Borodinova; Raad Tammo (Acta Medica Leopoliensia)
Aim. In patients with cyanotic congenital heart defects, pulmonary blood flow is maintained by a functioning patent ductus arteriosus (PDA). Most patients with complex duct-dependent cyanotic defects require intermediate palliative treatment before proceeding of total repair. Timely and complex outpatient monitoring by a pediatrician and pediatric cardiologist are important for patient survival following palliative treatment, along with determining optimal timing for consultations at specialized cardiac surgical centers. To present the outcomes of two methods for increasing pulmonary blood flow (systemic-to-pulmonary artery shunt (SPAS) and stenting of patent ductus arteriosus (PDA st.)), as well as the features of outpatient cardiological observation and treatment in these patients.